Transistores de efeito de campo baseados em grafeno crescido por CVD como uma plataforma para biossensores - Thiago Alonso Stephan Lacerda de Sousa (2014)
Graphene can be applied in the detection of substances ranging from gas to complex biomolecules such as DNA. Although graphene sensors are highly sensitive, it does not imply that they are also selective. The selectivity problem can be solved by modifying the material surface by functionalization. This work aims at the fabrication of devices that can be mass produced using commercial CVD grown graphene. We developed the transfer of graphene films to Si/SiO2 substrates, we fabricated field effect transistor (FET) devices by photolithography using direct laser writing and performed characterization by Raman spectroscopy and by electrical transport measurements. An extensive characterization of the electrical transport properties of the devices without functionalization and functionalized with Thionine or PBSE molecules was performed. Results show that both compounds are bonded to graphene surface and that Thionine functionalization promotes a significant n type doping in the material and also produces a decrease in the mobility of charge carriers in the devices. Functionalization with PBSE does not produce the very same doping effect. Both Thionine and PBSE are capable of modifying graphene surface in order to provide the immobilization of the aptamer with high affinity and specificity for the target protein. The experiments indicated the occurrence of a high sensitivity to the detection of Taq DNA polymerase protein linked to its specific antibody. We conclude that the strategy of functionalization of graphene surface to attach specific antibodies can lead to a sensing platform with high sensitivity and selectivity.